C‐reactive protein perturbs alveolar bone homeostasis: An experimental study of periodontitis and diabetes in the rat. (19th July 2022) - Zhou, Mengjiao; Xu, Xiaohui; Li, Jie; Zhou, Jie; He, Yao; Chen, Ziqi; Liu, Shan; Chen, Duanjing; Li, Han; Li, Guangyue; Huang, Jiao; Yang, Gangyi; et al.
Abstract: Aim: To explore the role of C‐reactive protein (CRP) in periodontitis and diabetes and its mechanism in alveolar bone homeostasis. Materials and Methods: In vivo, normal, and Crp knockout (KO) rats were randomly divided into control, diabetes, periodontitis, and diabetes and periodontitis groups, respectively. The diabetes model was established using a high‐fat diet combined with streptozotocin injection. The periodontitis model was established by ligature combined with lipopolysaccharide (LPS) injection. Alveolar bones were analysed using micro‐computed tomography, histology, and immunohistochemistry. In vitro, human periodontal ligament cells (hPDLCs) were treated with LPS and high glucose. CRP knockdown lentivirus or CRP overexpression adenovirus combined with a PI3K/AKT signalling inhibitor or agonist were used to explore the regulatory mechanism of CRP in osteogenesis and osteoclastogenesis of hPDLCs, as evidenced by alkaline phosphatase staining, Western blot, and quantitative polymerase chain reaction. Results: In periodontitis and diabetes, CRP KO decreased the alveolar bone loss and the expression levels of osteoclastogenic markers, while increasing the expression levels of osteogenic markers. CRP constrained osteogenesis while promoting the osteoclastogenesis of hPDLCs via PI3K/AKT signalling under high glucose and pro‐inflammatory conditions. Conclusions: CRP inhibits osteogenesis and promotes osteoclastogenesis via PI3K/AKT signalling under diabetic and pro‐inflammatory conditions, thus perturbing alveolar bone homeostasis.